Crisis in the US presidential social-commercial policy and its effects on the Mexican economy (GEON Journal (Management, Organizations and Business), 2017)
During the last 10 years there has been an increase in the contradictions in the commercial economic policy of the presence of the United States towards México, resulting in an instability in the commercial relationship between both countries. Nowadays, the proposals of the two presidential candidates to the White House especially the commercial policy and a little monitoring by the Mexican Federal Government. The work presented emphasizes the commercial proposals of Donald Trump and, secondly, the hidden interests of Hillary Clinton.The challenge of analysis is greater given the recurrent crises of the North American Economy in real estate and financial crisis especially the increase of its internal debt and past due portfolio as well as the increase of remittances to our country. The aim is to identify the contradictions of the North American presidential economic-commercial policy and its effects on México regarding the economic and financial crisis of both countries, a goal that has been concluded, under the research line of the International Economic and Financial Crisis, as a relevant result -Commercial of the United States has sharpened the contradictions of recurring crises in the United States and the United States, generating new processes of capital accumulation, and as a pressing conclusion is presented that the socioeconomic policy of the US government and its presidential increases the factors of economic and financial crisis.JEL A: 13, D: 60, F: 18, N: 35
Keywords: economic-commercial policy; internal debt; financial crisis